Characterization of a novel β-agarase from Antarctic macroalgae-associated bacteria metagenomic library and anti-inflammatory activity of the enzymatic hydrolysates - Gu, Xiaoqian; Zhao, Luying; Tan, Jiaojiao; Zhang, Qian; Fu, Liping; Li, Jiang (Frontiers in Microbiology, 2022)
An agarase gene (aga1904) that codes a protein with 640 amino acids was obtained from the metagenomic library of macroalgae-associated bacteria collected from King George Island, Antarctica. Gene aga1904 was expressed in Escherichia coli BL21 (DE3) and recombinant Aga1904 was purified by His Bind Purification kit. The optimal temperature and pH for the activity of Aga1904 were 50°C and 6.0, respectively. Fe3+ and Cu2+ significantly inhibited the activity of Aga1904. The Vmax and Km values of recombinant Aga1904 were 108.70 mg/mL·min and 6.51 mg/mL, respectively. The degradation products of Aga1904 against agarose substrate were mainly neoagarobiose, neoagarotetraose, and neoagarohexaose analyzed by thin layer chromatography. The cellular immunoassay of enzymatic hydrolysates was subsequently carried out, and the results showed that agaro-oligosaccharides dominated by neoagarobiose significantly inhibited key pro-inﬂammatory markers including nitric oxide (NO), interleukins 6 (IL-6) and tumor necrosis factor (TNF-α). This work provides a promising candidate for development recombinant industrial enzyme to prepare agaro-oligosaccharides, and paved up a new path for the exploitation of natural anti-inflammatory agent in the future.